Clinicopathologic Effects of Xenogeneic GvHD Induced by Adoptively Transferred Human-Derived T Cells in Severely Immunodeficient Mice - Ashraf, Hami; Kosari, Farid; Khorsand, Amir Arsalan; Muhammadnejad, Samad; Mansouri, Vahid; Muhammadnejad, Ahad; Ahmadbeigi, Naser; Monzavi, Seyed Mostafa (Archives of Iranian medicine, 2024)
Background: Xenogeneic graft-versus-host disease (xGvHD) is an inevitable confounder of preclinical evaluation of adoptive immunotherapies on tumor-bearing immunodeficient mouse models. This study was designed to appraise the clinical and histopathological effects caused by xGvHD in severely immunodeficient mice considering the T cell dosage. Methods: Fifty NOG mice underwent intraperitoneal injection of three different doses of human-derived total T cells, a high dose of CD8+T cells, or vehicle (as control). Clinical and histopathological status of the study subjects were evaluated and compared according to scoring systems. Results: In mice receiving higher doses of total T cells, the clinical severity of xGvHD was greater. However, recipients of CD8+T cells developed none to mild xGvHD manifestations. Higher doses of T cells were associated with poorer outcomes including premature death and more severe histopathologic damages. Greater CD3+T cell tissue engraftment (immunohistochemical CD3 positivity) was associated with more severe xGvHD-induced histopathological damages. Clinical xGvHD scores were significantly correlated with histopathological xGvHD scores in total and in each tissue. Mice with severe cutaneous symptoms had higher scores of xGvHD-induced histopathologic changes in the skin. Lethargy was associated with higher histopathological scores in the lungs, liver and spleen. Conclusion: In preclinical evaluations, lower doses of T cell-based therapies are associated with milder xGvHD. Development of xGvHD may be averted by the use of CD4+T cell-depleted grafts. Histopathological and clinical scoring systems for evaluating xGvHD are significantly correlated. The lungs and liver are reliable organs for histopathological assessment and scoring of xGvHD.